Policymaking in an age of polycrises: emerging perspectives - Bishoy L. Zaki; Valérie Pattyn; Ellen Wayenberg (Policy Design and Practice)
Policymaking has witnessed significant changes over the past decades, most of which stem from perturbations in the context where policy is made. These developments have emphasized considerable shortcomings of conventional approaches to both theories and practices of policymaking, whether in terms of policy design or analysis. Accordingly, several new theoretical approaches emerged to better understand the new reality of policymaking, including wickedness, turbulence and crises. While the crisis approach has become one of the strongest and fastest growing, research on crises rarely addresses the ever so pressing notion of “polycrises”, i.e. situations where crises intersect, overlap, and spill over into one another. This is despite polycrises becoming more frequent in scale, intense in magnitude and having significant influence on policymaking processes and outcomes. Sparing a handful of exceptions, the embryonic research on polycrises approaches the concept as a capacious semantic label, devoid of analytical utility, while policymakers use the term in a politicized manner that invokes urgency, without significant reflections on its implications for practice. This special collection contributes to the development of literature on polycrises by advancing its analytical utility as a promising lens to policy design, analysis and crisis governance, while illustrating its implications both for future research and practice.